Research priorities of the European Society of Clinical Pharmacy (ESCP): a questionnaire-based study - Okuyan, Betul; Henman, Martin C; Paudyal, Vibhu; Weidmann, Anita E; Cadogan, Cathal; Hazen, Ankie; Fialová, Daniela; Wirth, Francesca; Lutters, Monika; Pouls, Bart; Nazar, Zachariah; Al Raisi, Fatma; et al. (International journal of clinical pharmacy, 2025)
INTRODUCTION: It is important for health professional societies to involve members in defining their roles and future activities including research priorities. AIM: This study aimed to identify members' views on the areas of research that European Society of Clinical Pharmacy (ESCP) should prioritise in delivering research support, research projects and education. METHOD: An online questionnaire was initially developed by the ESCP Research Committee and reviewed by the research team. It included structured and open-ended items related to respondents' demographics, research experience, views on future research priorities, topics that ESCP should prioritise, and barriers to research involvement. After testing face and content validity, the questionnaire was sent to all ESCP members (N = 417). Descriptive statistics and summative content analysis were used. RESULTS: Eighty-two responses were received (response rate: 19.7%). Research on real-world processes that facilitate the implementation of clinical pharmacy services into every-day practice was the priority for most respondents (n = 77, 93.9%). Respondents believed that ESCP should focus on research support for implementation science (n = 52, 63.4%) and methods to analyse clinical judgement and decision-making (n = 48, 58.5%). The perceived barriers to developing high-quality research in clinical pharmacy were reported as a lack of knowledge, skills and training, limited funding opportunities and insufficient time. CONCLUSION: Research topics identified will help to inform ESCP and its committees on the priorities for research activities of the society in the near future, as well as other collaborating professional organisations of the current priority research objectives of ESCP in the international context.
Keywords: Research priorities; Clinical pharmacist; Barriers; European Society of Clinical Pharmacy